Heat-shrinkable fiber web reinforced large-span box arch C80 high-toughness concrete and preparation method thereof
By combining heat-shrinkable fiber mesh and multi-scale fibers in concrete, a three-dimensional reinforced network structure is formed, which solves the problems of brittleness and crack resistance of traditional high-strength concrete, and multiple improvements of high-performance concrete are achieved, including tensile and pressure resistance. and significantly improved crack resistance.
Patent Information
- Application Number
- CN202411425233.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Traditional high-strength concrete has high brittleness and poor crack resistance. A single type of fiber reinforcement is difficult to meet the multiple needs of modern engineering for high-performance concrete.
The heat-shrinkable fiber mesh is combined with multi-scale fibers (calcium carbonate whiskers, copper-plated straight steel fibers, multi-anchor point steel fibers, and heat-shrinkable fibers) to form a three-dimensional reinforced network structure in the concrete through the three-dimensional fiber mesh, which optimizes the high-level The aluminum phase gelling materials and hydration process utilize the heat shrinkage effect of heat shrink fibers and the bridge effect of CaCO3 whiskers to improve the tensile, compressive and crack resistance of concrete.
It significantly improves the bending toughness, compressive strength and durability of concrete, reduces early shrinkage cracks and maintenance costs, and improves the comprehensive performance and volume stability of concrete.
Smart Images

Figure BDA0005081960630000201 
Figure BDA0005081960630000211 
Figure FDA0005081960620000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete and a preparation method thereof. Background Art
[0002] Traditional high-strength concrete has some inherent defects, such as: High brittleness: Concrete is prone to brittle fracture when under tension and lacks sufficient ductility and toughness. Poor crack resistance: Concrete is prone to cracks during use, especially when there is a large concentration of forces (hanging basket construction) or environmental changes (large temperature difference between day and night in mountainous areas). Traditional fiber-reinforced concrete usually only uses a single type of fiber, such as metal fiber, glass fiber, heat-shrinkable organic fiber, basalt fiber, etc. Although these single chopped fibers can improve the toughness and crack resistance of concrete to a certain extent, due to the limited action mechanism and reinforcement effect of each fiber, it is difficult to meet the multiple demands of modern engineering for high-performance concrete and ultra-high-performance concrete.
[0003] Based on the existing problems in fiber reinforced concrete, it is necessary to improve it. Summary of the invention
[0004] In view of this, the present invention proposes a heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete and a preparation method thereof, so as to solve or partially solve the problems existing in the prior art.
[0005] In the first aspect, the present invention provides a heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete, comprising the following raw materials: high-aluminum phase cementitious material 580-640kg / m 3 , Fine aggregate 750~850kg / m 3 , high strength coarse aggregate 950~1100kg / m 3 , fiber reinforced materials 40~80kg / m 3 , heat shrinkable fiber mesh 3~8kg / m 3 , Special admixture for viscosity reduction and collapse prevention 9~11kg / m 3 , Water 140~160kg / m 3 .
[0006] Preferably, the special admixture for reducing viscosity and preventing collapse comprises a mother solution of a polycarboxylic acid high-efficiency water-reducing agent, an air entraining agent, a retarder, boric acid, a tetramethyldecynediol foam control agent, an acrylic acid-modified organosilicon defoamer and water;
[0007] The mass ratio of polycarboxylic acid high-efficiency water-reducing agent mother liquor, air entraining agent, retarder, boric acid, tetramethyldecynediol foam control agent, acrylic acid modified silicone defoaming agent and water is (52-56):(0.03-0.05):(1-2.5):(1.5-1.9):(0.05-0.2):(0.03-0.07):(33.65-35.15).
[0008] Preferably, the heat-shrinkable fiber mesh is a mesh structure woven from heat-shrinkable fibers, and the heat-shrinkable fibers include a heat-shrinkable core material and a heat-shrinkable skin material coated on the periphery of the heat-shrinkable core material;
[0009] The material of the heat shrinkable leather material includes at least one of polyvinyl alcohol, polyethylene, and polyoxymethylene;
[0010] The molecular weight of the polyvinyl alcohol is 170,000 to 220,000;
[0011] The molecular weight of the polyethylene is 1 million to 2 million;
[0012] The molecular weight of the polyoxymethylene is 20,000 to 30,000;
[0013] The heat shrinkable core material is made of polypropylene, and the molecular weight of polypropylene is 6000-8000;
[0014] The heat-shrinkable fiber has a tensile strength of 500-1200 MPa, an elastic modulus of 7-35 GPa, a shrinkage rate of 0.5%-12%, and a response temperature of 30°C-100°C.
[0015] Preferably, the high-aluminum phase cementitious material comprises a mixture of P·II 52.5 silicate cement, P·II 42.5 sulphoaluminate high-iron phase cement, fly ash microspheres and silica fume;
[0016] The P·II 42.5 sulphoaluminate high iron phase cement is a P·II 42.5 high iron phase sulphoaluminate cement containing a Q phase;
[0017] The fly ash microbeads have a 28d activity index of 109% and a water requirement ratio of 101%;
[0018] The SiO2 mass content in the silica ash is ≥90%, and the specific surface area is ≥20300m 2 / kg, 28d activity index ≥100%.
[0019] Preferably, the P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method:
[0020] Mix fly ash, limestone, magnesite and calcium sulfate to obtain a first mixed material;
[0021] The first mixed material is heated to 1290-1350° C. at a rate of 5-10° C. / min, and calcined for 40-45 minutes to obtain Q phase-calcium sulfoaluminate clinker;
[0022] Mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture;
[0023] The second mixed material is heated to 1290-1350°C at a rate of 5-10°C / min and calcined, and kept at this temperature for 40-45 minutes to obtain Sulphoaluminate cement clinker;
[0024] Q phase-calcium sulphoaluminate clinker, The sulphoaluminate cement clinker was mixed to obtain the Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0025] The Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker is mixed with dihydrate gypsum and ground to a specific surface area of 330-350m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained.
[0026] Preferably, the fiber reinforcement material includes copper-plated straight steel fiber, multi-anchor steel fiber, heat-shrinkable fiber, and CaCO3 whisker;
[0027] The mass ratio of the copper-plated straight steel fiber, the multi-anchor steel fiber, the heat-shrinkable fiber, and the CaCO3 whisker is (20-30):(20-30):(1-2):(10-15).
[0028] Preferably, the copper-plated straight steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.20 ± 0.02 mm, a breaking strength of ≥ 2200 MPa, an elastic modulus of 190 to 230 GPa, and a tensile strength of 400 to 2100 MPa;
[0029] The nominal length of the multi-anchor steel fiber is 6-13 mm, the equivalent diameter is 0.18±0.02 mm, the breaking strength is ≥1300 MPa, the elastic modulus is 220-240 GPa, and the tensile strength is 600-2200 MPa; the length of the heat-shrinkable fiber is 10 mm-12 mm, the tensile strength is 500-1200 MPa, the elastic modulus is 7-35 GPa, the shrinkage rate is 0.5%-12%, and the response temperature is 30°C-100°C;
[0030] The CaCO3 whisker has a nominal length of 10 to 20 μm, an elastic modulus of 410 to 710 GPa, and a tensile strength of 3000 to 6000 MPa.
[0031] Preferably, the mass ratio of fly ash, limestone, magnesite and calcium sulfate is (60-70):(15-20):(5-10):(5-10);
[0032] The mass ratio of the red mud, limestone, bauxite and calcium sulfate is (40-45):(25-30):(20-25):(5-10);
[0033] The Q phase-calcium sulphoaluminate clinker, The mass ratio of sulphoaluminate cement clinker is (50-60):(40-50);
[0034] The mass of the dihydrate gypsum is 10-15% of the mass of the Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker;
[0035] The amount of P·II 52.5 silicate cement added is 350-355 kg / m 3 , P·II 42.5 sulphoaluminate high iron phase cement addition amount is 150~155kg / m 3 , the amount of fly ash microbeads added is 80-90kg / m 3 , silica fume 30~40kg / m 3 .
[0036] Preferably, the fine aggregate is river sand with an apparent density of 2560-2650 kg / m 3 , fineness modulus is 2.8, water absorption ≤8%;
[0037] The high-strength coarse aggregate is 5-16mm continuously graded basalt ultra-high-strength coarse aggregate with an apparent density of 2900-3000kg / m 3 .
[0038] In a second aspect, the present invention further provides a method for preparing the heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete, comprising the following steps:
[0039] The high-aluminum phase cementitious material, fine aggregate and high-strength coarse aggregate are mixed and stirred for 60 to 120 seconds, and then water and 45 to 55% by weight of a special admixture for reducing viscosity and preventing collapse are added, and the stirring is continued; the fiber reinforcement material is then added, and after stirring, the remaining special admixture for reducing viscosity and preventing collapse is added to obtain a mixture;
[0040] The heat-shrinkable fiber mesh is fixed in the mold, and then the mixture is placed in the mold and vibrated to obtain the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete.
[0041] The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete and the preparation method thereof have the following beneficial effects compared with the prior art:
[0042] 1. The heat-shrinkable fiber mesh obtained by the present invention reinforces the C80 high-toughness concrete for large-span box arches, avoiding the traditional concrete reinforcement technology that mainly relies on a single type of fiber reinforcement and cannot comprehensively improve the comprehensive performance of concrete. The heat-shrinkable fiber mesh can effectively prevent the formation and expansion of cracks and improve the compressive strength of concrete by being evenly distributed and fixed inside the concrete matrix. The combination of multi-scale fibers (calcium carbonate whiskers, copper-plated straight steel fibers, multi-anchor steel fibers, heat-shrinkable fibers) and three-dimensional fiber mesh enables concrete to exhibit stronger tensile and flexural properties under tensile stress and bending stress. The three-dimensional fiber mesh forms a three-dimensional reinforced network structure in the concrete, which can effectively disperse and resist external stress, greatly improve the bending toughness of high-performance concrete, and absorb more energy without damage. Moreover, the combination of the three-dimensional fiber mesh and fiber-reinforced materials improves the crack resistance and durability of concrete, and reduces early shrinkage cracks and maintenance costs caused by environmental and load changes. By placing a three-dimensional fiber mesh in the mold in advance, the fiber mesh is ensured to be evenly distributed and fixed in the concrete, avoiding the problem that the existing high-dosage chopped fibers are easily unevenly distributed in the concrete, resulting in unsatisfactory fiber reinforcement effects and fiber agglomeration during construction.
[0043] 2. The heat-shrinkable fiber mesh reinforced large-span box-arch C80 high-toughness concrete obtained by the present invention increases the proportion of CASH gel in the cementitious slurry by optimizing the raw material composition and hydration process of the high-aluminum phase cementitious material, thereby realizing the toughening of the C80 concrete material at the nano-molecular scale; through the heat shrinkage effect of the heat-shrinkable fiber, when the early hydration heat of the high-strength concrete is too high, micro-precompression stress is generated through shrinkage, the early self-shrinkage of the concrete is reduced, and the toughness of the concrete is improved from the micro-nano scale; through the micro-scale effect of the CaCO3 whisker, the micro-cracks inside the concrete can be bridged, the porosity of the concrete can be reduced, and the toughness of the high-strength concrete can be improved from the micron scale; through the bridging effect of the copper-plated straight steel fiber and the multi-anchor steel fiber, the formation and expansion of cracks inside the concrete are delayed, and the toughness of the high-strength concrete is improved from the macroscopic millimeter level.
[0044] 3. The apparent density of the heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete obtained by the present invention is 2450-2650 kg / m 3 At the same time, the compressive strength grade can reach C90 or above. It has good working performance, mechanical properties and durability, can effectively improve the bending toughness, elastic modulus and volume stability of concrete components, and has important practical application value. DETAILED DESCRIPTION
[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0047] The present application provides a heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete, including the following raw materials: high-aluminum phase cementitious material 580-640kg / m 3 , Fine aggregate 750~850kg / m 3 , high strength coarse aggregate 950~1100kg / m 3 , fiber reinforced materials 40~80kg / m 3 , heat shrinkable fiber mesh 3~8kg / m 3 , Special admixture for viscosity reduction and collapse prevention 9~11kg / m 3 , Water 140~160kg / m 3 .
[0048] The present invention achieves multi-scale toughening of concrete for large-span reinforced concrete box arches by designing material composition and structure: by optimizing the raw material composition and hydration process of high-aluminum phase cementitious materials, the proportion of CASH gel in the cementitious slurry is increased, and the toughening of C80 concrete materials on the nano-molecular scale is achieved; the heat-shrinkable fibers in the fiber-reinforced materials are reconstructed by the molecular heat released by the hydration of the cementitious materials to produce shrinkage characteristics, and uniform pre-compression stress is applied inside the cementitious slurry by adding the heat-shrinkable fibers, and the toughening of C80 concrete materials on the micron scale is achieved by adding CaCO3 whiskers; the toughening of C80 concrete materials on the macro-scale is achieved by adding copper-plated straight steel fibers and multi-anchor steel fibers; by adding a heat-shrinkable fiber mesh in the steel bar protective layer of the large-span reinforced concrete box arch, the fiber mesh is stimulated by the hydration heat of the box arch concrete to shrink, and the pre-compression stress is further applied to the C80 concrete in the steel bar protective layer, thereby improving the toughness and crack resistance of the concrete. The application of micro prestress can effectively prevent the expansion of concrete cracks in the steel protection layer, thereby reducing the intrusion of moisture and harmful substances and preventing steel corrosion. The high-aluminum phase cementitious materials and special admixtures for reducing viscosity and preventing collapse can optimize the working performance of concrete and enhance its fluidity and homogeneity. In addition, the ratio of aluminum phase and gypsum in the high-aluminum phase cementitious materials is adjusted to promote the uniform distribution of the generated calcium sulfonate crystals in the CSH gel, while the magnesium hydroxide formed by the hydration of the Q phase and the Q phase hydration products are used. The further hydration of the formed calcium aluminate compensates the shrinkage of C80 concrete, realizing the volume stability design of C80 concrete. The high-toughness C80 concrete prepared by this technology can solve the problems of dense steel bars in large-span reinforced concrete box arches that are difficult to pump, high-strength concrete that is prone to shrinkage and cracking, and steel corrosion.
[0049] The present invention proposes fiber-reinforced materials and fiber mesh toughening technology to improve the toughness of concrete; Mg(OH)2 and calcium aluminate generated by the hydration of the Q phase in the high-iron phase of sulphoaluminate cement are used to compensate for shrinkage and heat-shrinkable fibers to synergistically improve the volume stability of concrete, thereby improving the crack resistance of concrete; traditional fiber-reinforced concrete usually only uses a single type of fiber, such as metal fiber, glass fiber, heat-shrinkable fiber, basalt fiber, etc. Although these single chopped fibers can improve the toughness and crack resistance of concrete to a certain extent, due to the limited action mechanism and reinforcement effect of each fiber, it is difficult to meet the multiple demands of modern engineering for high-performance concrete and ultra-high-performance concrete. Multi-scale fiber reinforced concrete uses different types and sizes of fibers in combination to exert the synergistic reinforcement effect of various fibers, thereby significantly improving the comprehensive performance of concrete; specifically: calcium carbonate whiskers as micrometer-scale fibers can bridge micro cracks in concrete, improve the porosity of concrete, and improve the density and crack resistance of the matrix; steel fibers as macro fibers have a bridging effect in concrete, enhancing the tensile strength and toughness index of the concrete matrix; heat-shrinkable fibers can expand or contract when the temperature changes, induce the release of stress inside the concrete, and reduce cracks caused by temperature stress. Introducing heat-shrinkable fiber mesh in multi-scale fiber reinforced concrete can further improve the toughness and crack resistance of concrete; three-dimensional fiber mesh has the following advantages: three-dimensional reinforcement structure: the three-dimensional fiber mesh forms a three-dimensional mesh structure in concrete, providing a multi-directional reinforcement effect; uniform distribution: the three-dimensional fiber mesh can be evenly distributed in concrete, avoiding fiber aggregation and improving the overall performance of concrete; high durability: the organic fiber mesh is not easily corroded, avoiding the problem of easy corrosion of steel bars in reinforced concrete.
[0050] The present invention adjusts the dosage of fly ash microbeads and the dosage of special admixtures for reducing viscosity and preventing collapse in high-aluminum phase cementitious materials to regulate the mechanical properties and working performance of concrete, thereby realizing a high-strength and high-fluidity design of concrete; the addition of fiber-reinforced materials and heat-shrinkable fiber nets can improve the toughness of concrete at multiple scales such as macro, millimeter and micro-nano, thereby realizing a high-toughness design of high-strength concrete; in addition, the temperature rise shrinkage characteristics of magnesium hydroxide, calcium aluminate and heat-shrinkable fibers generated by hydration of the Q phase in sulphoaluminate high-iron phase cement are utilized to reduce the shrinkage of concrete and improve the volume stability and crack resistance of concrete. The heat-shrinkable fiber net reinforced large-span box arch C80 high-toughness concrete of the present invention has high strength, high toughness, high fluidity and high durability, solves the problem of easy corrosion of steel bars in reinforced concrete and insufficient toughness of high-strength concrete, and has important practical application value.
[0051] In some embodiments, the special admixture for reducing viscosity and preventing collapse includes a mother solution of a polycarboxylic acid high-efficiency water-reducing agent, an air entraining agent, a retarder, boric acid, a tetramethyldecynediol foam control agent, an acrylic acid-modified organosilicon defoamer, and water;
[0052] The mass ratio of polycarboxylic acid high-efficiency water-reducing agent mother liquor, air entraining agent, retarder, boric acid, tetramethyldecynediol foam control agent, acrylic acid modified silicone defoaming agent and water is (52-56):(0.03-0.05):(1-2.5):(1.5-1.9):(0.05-0.2):(0.03-0.07):(33.65-35.15).
[0053] Specifically, the mother liquor of polycarboxylic acid high-efficiency water-reducing agent has a high water-reducing rate and is used to improve the fluidity and strength of concrete; the air-entraining agent is used to introduce tiny bubbles below 100 μm to enhance workability; the retarder prolongs the retarding time of concrete and improves the collapse-preserving effect; the boric acid improves the setting time of concrete and ensures the workability of fresh concrete; the tetramethyldecynediol foam control agent stabilizes the air content of concrete and reduces the air loss during concrete pumping; the acrylic acid-modified organosilicon defoamer reduces the air content inside the concrete and controls the air content to about 3%; weigh the components of the above raw materials, use high-speed stirring equipment to fully mix the components, and obtain the special admixture for viscosity reduction and collapse preservation.
[0054] In some embodiments, the heat-shrinkable fiber mesh is a mesh structure woven from heat-shrinkable fibers, and the heat-shrinkable fibers include a heat-shrinkable core material and a heat-shrinkable skin material wrapped around the heat-shrinkable core material;
[0055] The material of the heat shrinkable leather material includes at least one of polyvinyl alcohol, polyethylene, and polyoxymethylene;
[0056] The molecular weight of polyvinyl alcohol is 170,000 to 220,000;
[0057] The molecular weight of polyethylene is 1 million to 2 million;
[0058] The molecular weight of polyoxymethylene is 20,000 to 30,000;
[0059] The material of the heat shrinkable core is polypropylene, and the molecular weight of polypropylene is 6000-8000;
[0060] The tensile strength of the heat-shrinkable fiber is 500-1200 MPa, the elastic modulus is 7-35 GPa, the shrinkage rate is 0.5%-12%, and the response temperature is 30°C-100°C.
[0061] Specifically, in some embodiments, the method for preparing the heat-shrinkable fiber comprises the following steps:
[0062] S1. Two extruders are used to extrude the heat shrinkable core material mixture and the heat shrinkable skin material mixture into a die head with two cavities, wherein the heat shrinkable skin material enters the cavity corresponding to the skin material, and the heat shrinkable core material enters the cavity corresponding to the core material. The materials in the two cavities converge at the position of the spinneret of the extruder; wherein the spinneret has an inner ring and an outer ring, the inner ring of the spinneret is connected to the cavity of the core material, and the outer ring of the spinneret is connected to the cavity of the skin material, and the two molten materials are extruded (melt extrusion) through the spinneret, and stick together in the air, cooled by a cold water tank, and then drawn in hot water at 90-100°C to form a composite fiber with a skin-core structure;
[0063] S2, adding 1%-5% (mass concentration) silane coupling agent solution to the composite fiber obtained in step S1 for modification for 10-20 minutes, and then drying and indenting the surface to enhance its bonding performance with concrete slurry;
[0064] S3, adding the composite fiber obtained in step S2 into a modified polyvinyl alcohol solution to which an expansion component is added for coating and modification, taking out and drying, thereby obtaining a heat-shrinkable fiber;
[0065] Among them, the heat shrinkable leather material mixture, each raw material and its mass percentage are: polyvinyl alcohol 97%, maleic anhydride grafted compatibilizer 1.5%, phthalate plasticizer 1.5%; the extrusion pressure of the leather material cavity is 8MPa, and the melting temperature is maintained at 250℃;
[0066] The heat shrinkable core material mixture, each raw material and its mass percentage are: polypropylene 98%, rigid nucleating agent 2% (aluminum aromatic carboxylate aluminum and sodium benzoate in a mass ratio of 1:1); the melting temperature of the heat shrinkable core material mixture is 200-280°C; the extrusion pressure of the corresponding cavity is 7-10MPa;
[0067] In the last extrusion section corresponding to the spinneret, the extrusion temperature of the two molten materials is maintained at a temperature suitable for both materials, that is, 200-220° C., and the extrusion pressure is 3-10 MPa.
[0068] In some embodiments, the coating modification temperature is room temperature and the time is 10 to 24 hours.
[0069] In some embodiments, the expansion agent is a compound of a calcium oxide expansion agent and a calcium sulfoaluminate expansion agent; preferably, the expansion agent is a compound of a calcium oxide expansion agent and a calcium sulfoaluminate expansion agent in a mass ratio of 1:40 to 50;
[0070] In some embodiments, the modified polyvinyl alcohol solution with added swelling component is obtained by uniformly mixing a polyvinyl alcohol solution (6 wt %) and a liquid swelling agent in a mass ratio of 7:3.
[0071] In some embodiments, a method for preparing a heat-shrinkable fiber web comprises the following steps:
[0072] The heat-shrinkable fibers (length of 20-50 mm and diameter of 20-100 microns) prepared above are woven into a fiber mesh using a warp knitting machine. The warp knitting machine sets a suitable weaving speed and tension to ensure the uniformity and stability of the fiber mesh. The fibers are arranged longitudinally and woven according to a set mesh size of 20 mm. The warp knitting process can ensure that the mesh size of the fiber mesh is consistent and neatly arranged. The fibers are arranged transversely and woven according to a set mesh size. The fibers are woven into a mesh using a knitting device, and the woven flat fiber mesh is shaped by heat treatment (the shaping temperature is 100-120°C and the time is 10-20 minutes) to stabilize the size and shape of the fiber mesh. In this way, a two-dimensional heat-shrinkable fiber mesh is formed. Lay a piece of two-dimensional fiber mesh flat on a workbench to ensure that it is flat and wrinkle-free. Fold once with a folding spacing of 20 mm, starting from one end and folding according to the spacing. When folding, an upward fold is formed, and then folded back downward to form a wavy structure. The folded shape can be a wavy shape with alternating "mountain shape" and "valley shape". Use hot melt adhesive to fix each fold to ensure the stability of the folded three-dimensional fiber mesh. After each fold is fixed, additional heat treatment is performed at the intersection between the crest and the trough to fix it. The fixed wavy fiber mesh is heat treated (temperature 110±10℃, time 12.5±2.5 minutes) to ensure that its shape and structure remain stable. By cross-weaving multiple two-dimensional fiber meshes together, an interlaced three-dimensional structure is formed.
[0073] In some embodiments, the high-alumina phase cementitious material includes a mixture of P·II 52.5 silicate cement, P·II 42.5 sulphoaluminate high-iron phase cement, fly ash microspheres and silica fume;
[0074] P·II 42.5 sulphoaluminate high iron phase cement is P·II 42.5 high iron phase sulphoaluminate cement containing Q phase;
[0075] The 28d activity index of fly ash microbeads is 109%, and the water requirement ratio is 101%;
[0076] The SiO2 mass content in silica fume is ≥90%, and the specific surface area is ≥20300m 2 / kg, 28d activity index ≥100%.
[0077] P·II 42.5 sulphoaluminate high iron phase cement is a P·II high iron phase sulphoaluminate cement containing Q phase, which is calcined at 1290-1350℃ and has a mineral composition of 25%-30% Q phase minerals (Ca 20 Al 26 Mg3Si3O 68 ), 40%-45% The clinker of mineral, 20%-25% C4AF mineral, 0%-5% C2S mineral and 10%-15% dihydrate gypsum are ground together to a specific surface area of 330-350m 2 / kg prepared.
[0078] In some embodiments, the P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method:
[0079] S1, mixing fly ash, limestone, magnesite and calcium sulfate to obtain a first mixture;
[0080] S2, heating the first mixed material to 1290-1350° C. at a rate of 5-10° C. / min, calcining the mixture, and keeping the temperature for 40-45 min to obtain Q phase-calcium sulfoaluminate clinker;
[0081] S3, mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture;
[0082] S4, the second mixed material is heated to 1290-1350°C at 5-10°C / min and calcined, and kept at this temperature for 40-45 minutes to obtain Sulphoaluminate cement clinker;
[0083] S5, Q phase - calcium sulphoaluminate clinker, The sulphoaluminate cement clinker was mixed to obtain the Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0084] S6. Mix the Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker with dihydrate gypsum and grind it to a specific surface area of 330-350m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained.
[0085] In some embodiments, the fiber reinforcement material includes copper-coated straight steel fibers, multi-anchor steel fibers, heat-shrinkable fibers, and CaCO3 whiskers;
[0086] The mass ratio of copper-plated straight steel fiber, multi-anchor steel fiber, heat-shrinkable fiber, and CaCO3 whisker is (20-30):(20-30):(1-2):(10-15).
[0087] In some embodiments, the copper-coated straight steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.20 ± 0.02 mm, a breaking strength of ≥ 2200 MPa, an elastic modulus of 190 to 230 GPa, and a tensile strength of 400 to 2100 MPa;
[0088] The nominal length of the multi-anchor steel fiber is 6-13 mm, the equivalent diameter is 0.18±0.02 mm, the breaking strength is ≥1300 MPa, the elastic modulus is 220-240 GPa, and the tensile strength is 600-2200 MPa;
[0089] The preparation method of the heat-shrinkable fiber is the same as above. The heat-shrinkable fiber has a length of 10 mm to 12 mm, a tensile strength of 500 to 1200 MPa, an elastic modulus of 7 to 35 GPa, a shrinkage rate of 0.5% to 12%, and a response temperature of 30°C to 100°C.
[0090] The nominal length of CaCO3 whiskers is 10-20 μm, the elastic modulus is 410-710 GPa, and the tensile strength is 3000-6000 MPa.
[0091] In some embodiments, the mass ratio of fly ash, limestone, magnesite, and calcium sulfate is (60-70):(15-20):(5-10):(5-10);
[0092] The mass ratio of red mud, limestone, bauxite and calcium sulfate is (40-45):(25-30):(20-25):(5-10);
[0093] Q phase - calcium sulphoaluminate clinker, The mass ratio of sulphoaluminate cement clinker is (50-60):(40-50);
[0094] The mass of dihydrate gypsum is 10-15% of the mass of Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker;
[0095] P·II 52.5 Portland cement addition amount is 350~355kg / m 3 , P·II 42.5 sulphoaluminate high iron phase cement addition amount is 150~155kg / m 3 , the amount of fly ash microbeads added is 80-90kg / m 3 , silica fume 30~40kg / m 3 .
[0096] In some embodiments, the fine aggregate is river sand with an apparent density of 2560-2650 kg / m 3 , fineness modulus is 2.8, water absorption ≤8%;
[0097] High-strength coarse aggregate is 5-16mm continuously graded basalt ultra-high-strength coarse aggregate with an apparent density of 2900-3000kg / m 3 .
[0098] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete, comprising the following steps:
[0099] S1. Mix high-aluminum phase cementitious material, fine aggregate and high-strength coarse aggregate and stir for 60 to 120 seconds, then add water and 45 to 55% by weight of a special admixture for reducing viscosity and preventing collapse, and continue stirring; then add fiber reinforcement material, stir and then add the remaining special admixture for reducing viscosity and preventing collapse to obtain a mixture;
[0100] S2. Fix the heat-shrinkable fiber mesh in the mold, and then place the mixture in the mold and vibrate it to obtain the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete.
[0101] In some embodiments, high-aluminum phase cementitious material, fine aggregate, and high-strength coarse aggregate are mixed and stirred for 60 to 120 seconds, and then water and a portion of the special admixture for reducing viscosity and preventing collapse (45 to 55% of the special admixture for reducing viscosity and preventing collapse) are added, and stirring is continued; fiber reinforcement material is added, and the remaining special admixture for reducing viscosity and preventing collapse is added after stirring for 30 seconds. The cut heat-shrinkable fiber mesh is placed in a clean mold, and the hot melt glue is heated to an appropriate temperature using a hot melt glue gun, and the hot melt glue is applied to the side walls of the mold. The edge of the three-dimensional fiber mesh is pasted on the side wall of the mold to fix it. The two ends of each fiber grid are fixed with hot melt glue to ensure its structural stability; the mixture is placed in the mold and vibrated to obtain the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete.
[0102] The principle of the present invention is:
[0103] 1. The heat-shrinkable fiber mesh obtained by the present invention reinforces the C80 high-toughness concrete of the large-span box arch, avoiding the traditional concrete reinforcement technology that mainly relies on a single type of fiber reinforcement and cannot comprehensively improve the comprehensive performance of concrete. The heat-shrinkable fiber mesh can effectively prevent the formation and expansion of cracks and improve the compressive strength of concrete by being evenly distributed and fixed inside the concrete matrix. The combination of multi-scale fibers (calcium carbonate whiskers, copper-plated straight steel fibers, multi-anchor steel fibers, heat-shrinkable fibers) and three-dimensional fiber mesh enables concrete to show stronger tensile and flexural properties under tensile stress and bending stress. The three-dimensional fiber mesh forms a three-dimensional reinforced network structure in the concrete, which can effectively disperse and resist external stress, greatly improve the bending toughness of high-performance concrete, and absorb more energy without damage. And the combination of three-dimensional fiber mesh and fiber-reinforced materials improves the crack resistance and durability of concrete, and reduces early shrinkage cracks and maintenance costs caused by environmental and load changes. By placing a three-dimensional fiber mesh in the mold in advance, the fiber mesh is ensured to be evenly distributed and fixed in the concrete, avoiding the problem that the existing high-dosage chopped fibers are easily unevenly distributed in the concrete, resulting in unsatisfactory fiber reinforcement effects and fiber agglomeration during construction.
[0104] 2. The addition of heat-shrinkable fiber mesh improves the problem of easy corrosion of steel bars. As an organic synthetic material, heat-shrinkable fiber mesh itself has excellent corrosion resistance, especially in acid, alkali and salt environments; high-toughness fiber concrete has extremely high crack resistance and can form a more compact structure with smaller porosity, which can reduce the penetration of water and chloride ions, thereby further protecting the internal steel bars. Therefore, adding heat-shrinkable fiber mesh to the protective layer of reinforced concrete can effectively prevent steel bars from rusting.
[0105] 3. The viscosity of concrete is synergistically regulated by utilizing the "ball effect" of fly ash microspheres in high-aluminum phase cementitious materials and the mother liquor of polycarboxylic acid water-reducing agent in the special admixture for viscosity reduction and collapse protection, thereby optimizing the workability of fresh concrete and allowing the concrete to fill the gaps in the heat-shrinkable fiber mesh, thereby improving the density of concrete and achieving a high-flowability, high-toughness and high-durability design of concrete; the Q phase in the sulfoaluminate high-iron phase cement is hydrated to generate magnesium hydroxide and calcium aluminate; when the internal hydration heat of concrete is too large in the early stage, the heat-shrinkable fibers generate micro-stresses through heat, and the two synergistically reduce the early self-shrinkage and drying shrinkage of concrete, thereby improving the volume stability of high-strength concrete.
[0106] The apparent density of the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete obtained by the present invention is 2450-2650 kg / m 3At the same time, the compressive strength can reach more than 90MPa, and the flexural strength can reach more than 10MPa. It has good working performance, mechanical properties and durability, can effectively improve the bending toughness, elastic modulus and volume stability of concrete components, and has important practical application value.
[0107] The following further illustrates the heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete and its preparation method of the present invention with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as a limitation of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0108] In the following embodiments, the heat-shrinkable fiber web is obtained by weaving heat-shrinkable fibers, wherein the preparation method of the heat-shrinkable fibers comprises the following steps:
[0109] S1. Two extruders are used to extrude the heat shrinkable core material mixture and the heat shrinkable skin material mixture into a die head with two cavities, wherein the heat shrinkable skin material enters the cavity corresponding to the skin material, and the heat shrinkable core material enters the cavity corresponding to the core material. The materials in the two cavities converge at the position of the spinneret of the extruder; wherein the spinneret has an inner ring and an outer ring, the inner ring of the spinneret is connected to the cavity of the core material, and the outer ring of the spinneret is connected to the cavity of the skin material, and the two molten materials are extruded (melt extrusion) through the spinneret, and stick together in the air, cooled by a cold water tank, and then drawn in 95°C hot water to form a composite fiber with a skin-core structure;
[0110] S2, adding 3% (mass concentration) silane coupling agent (specifically octamethylcyclotetrasiloxane) solution to the composite fiber obtained in step S1 for modification for 20 minutes, and then drying and indenting the surface to enhance its bonding performance with the concrete slurry;
[0111] S3, adding the composite fiber obtained in step S2 to a modified polyvinyl alcohol solution with an expansion component added thereto, and performing coating modification at room temperature for 20 hours, taking it out and drying it, so as to obtain a heat-shrinkable fiber; the modified polyvinyl alcohol solution with an expansion component added thereto is obtained by uniformly mixing a polyvinyl alcohol solution (6wt%) and an expansion agent at a mass ratio of 7:3, and the expansion agent is a composite of a calcium oxide expansion agent and a calcium sulfoaluminate expansion agent at a mass ratio of 1:45;
[0112] Among them, the heat shrinkable leather material mixture, each raw material and its mass percentage are: polyvinyl alcohol 97%, maleic anhydride grafted compatibilizer (model provided by Dongguan Shenghao Plastic Raw Materials Co., Ltd., model PP-G-MAH) 1.5%, phthalate plasticizer 1.5%; the extrusion pressure of the leather material cavity is 8MPa, and the melting temperature is maintained at 250°C;
[0113] The heat shrinkable core material mixture, each raw material and its mass percentage are: polypropylene 98%, rigid nucleating agent 2% (aluminum aromatic carboxylate aluminum and sodium benzoate in a mass ratio of 1:1); the melting temperature of the heat shrinkable core material mixture is 210°C; the extrusion pressure of the corresponding cavity is 8MPa;
[0114] In the last extrusion section corresponding to the spinneret, the extrusion temperature of the two molten materials is maintained at a temperature suitable for both materials, i.e., 215°C, and the extrusion pressure is 6MPa;
[0115] The average diameter of the obtained core fiber is 0.15 mm, and the thickness of the skin fiber is 0.08 mm;
[0116] The obtained heat-shrinkable fiber has a length of 10 mm to 12 mm, a shrinkage rate of 0.5% to 12%, a response temperature of 30° C. to 100° C., a tensile strength of 700 MPa, and an elastic modulus of 15.0 GPa.
[0117] Example 1
[0118] This embodiment provides a heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete, including the following raw materials: high-aluminum phase cementitious material 630kg / m 3 , fine aggregate 805kg / m 3 , high strength coarse aggregate 1025kg / m 3 , fiber reinforced material 63.5kg / m 3 , Heat shrinkable fiber mesh 3kg / m 3 , Special admixture for reducing viscosity and preventing collapse 10.4kg / m 3 , water 151kg / m 3 ;
[0119] Special admixtures for reducing viscosity and preventing collapse include polycarboxylic acid high-efficiency water-reducing agent mother liquor, air entraining agent, retarder, boric acid, tetramethyldecynediol foam control agent, acrylic acid modified silicone defoamer and water;
[0120] The mass ratio of polycarboxylic acid high-efficiency water-reducing agent mother liquor, air-entraining agent, retarder, boric acid, tetramethyldecynediol foam control agent, acrylic acid-modified silicone defoamer and water is 54:0.04:2:1.7:0.1:0.05:34;
[0121] The mother liquor of polycarboxylate water reducer is The mother liquor of polycarboxylic acid highly adaptable water reducing agent is produced by Jiangsu Subot New Materials Co., Ltd.; the air entraining agent is High-efficiency air-entraining agent for concrete, produced by Jiangsu Subote New Materials Co., Ltd.; retarder is Concrete retarder, produced by Jiangsu Subot New Materials Co., Ltd.; boric acid is a white crystalline powder, produced by Fangzheng Reagent Factory, Beichen District, Tianjin; tetramethyldecynediol foam control agent is produced by Jiangsu Subot New Materials Co., Ltd.; acrylic acid modified silicone defoamer is specifically Type defoamer, produced by Jiangsu Subote New Materials Co., Ltd.;
[0122] High alumina cementitious materials include P·II 52.5 silicate cement (352.8kg / m 3 ), P·II 42.5 sulphoaluminate high iron phase cement (151.2kg / m 3 ), fly ash microbeads (88.2kg / m 3 ) and silica fume (37.8kg / m 3 )
[0123] P·II 42.5 sulphoaluminate high iron phase cement is P·II 42.5 high iron phase sulphoaluminate cement containing Q phase;
[0124] The 28d activity index of fly ash microbeads is 109%, and the water requirement ratio is 101%;
[0125] The SiO2 mass content in silica fume is ≥90%, and the specific surface area is ≥20300m 2 / kg, 28d activity index ≥100%.
[0126] P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method:
[0127] S1, mixing fly ash, limestone, magnesite and calcium sulfate to obtain a first mixture; the mass ratio of fly ash, limestone, magnesite and calcium sulfate is 60:20:5:10;
[0128] S2, heating the first mixed material to 1330° C. at a rate of 5° C. / min and calcining the mixture, and keeping the temperature for 40 min to obtain Q phase-calcium sulfoaluminate clinker;
[0129] S2, mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture; the mass ratio of red mud, limestone, bauxite and calcium sulfate is 45:25:25:5;
[0130] S3, the second mixed material is heated to 1300°C at 5°C / min and calcined, and kept at this temperature for 45 minutes to obtain Sulphoaluminate cement clinker;
[0131] S4, Q phase - calcium sulphoaluminate clinker, The sulphoaluminate cement clinker is mixed in a mass ratio of 50:50 to obtain a Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0132] S5, after mixing the Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker with dihydrate gypsum, grind it to a specific surface area of 340m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained; the mass of dihydrate gypsum is 10% of the mass of Q-phase-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0133] Fiber reinforcement includes copper-coated straight steel fibers (26 kg / m 3 ), multi-anchor steel fiber (26kg / m 3 ), heat shrinkable fiber (1kg / m 3 )、CaCO3 whiskers (10.5kg / m 3 );
[0134] The copper-plated straight steel fiber is produced by Wuhan Xintu Engineering New Materials Technology Co., Ltd., with a nominal length of 13 mm, an equivalent diameter of 0.20 ± 0.02 mm, a breaking strength of ≥ 2200 MPa, an elastic modulus of 210 GPa, and a tensile strength of 1300 MPa;
[0135] The multi-anchor steel fiber is produced by Wuhan Xintu Engineering New Materials Co., Ltd., with a nominal length of 13 mm, an equivalent diameter of 0.2 ± 0.02 mm, a breaking strength ≥ 1200 MPa, an elastic modulus of 220 GPa, and a tensile strength of 1400 MPa;
[0136] The preparation method of the heat-shrinkable fiber is the same as above. The heat-shrinkable fiber has a length of 12 mm, a shrinkage rate of 0.5% to 12%, a response temperature of 30°C to 100°C, a tensile strength of 700 MPa, and an elastic modulus of 15.0 GPa;
[0137] The CaCO3 whiskers were produced by Chuangbo Products Co., Ltd. in Lingshou County, Hebei Province, with a nominal length of 15 μm, an elastic modulus of 610 Gpa, and a tensile strength of 4500 Mpa;
[0138] The fine aggregate is river sand, and the apparent density of fine aggregate is 2600kg / m 3 , fineness modulus is 2.8, water absorption ≤8%;
[0139] High-strength coarse aggregate is basalt coarse aggregate with continuous grading of 5-16 mm. The strength of basalt coarse aggregate is 169 MPa, the crushing value is 10%, the needle-like content is ≤5%, and the apparent density is 3000 kg / m 3 .
[0140] The method for preparing the above-mentioned heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete comprises the following steps:
[0141] S1. Mix high-aluminum phase cementitious material, fine aggregate and high-strength coarse aggregate and stir for 100 seconds, then add water and 50% by weight of a special admixture for reducing viscosity and preventing collapse, and continue stirring; then add fiber reinforcement material, stir for 30 seconds, and then add the remaining special admixture for reducing viscosity and preventing collapse to obtain a mixture;
[0142] S2. Fix the heat-shrinkable fiber mesh in the mold, and then place the mixture in the mold and vibrate it to obtain the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete.
[0143] Example 2
[0144] The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete provided in the embodiment of the present application is the same as that in embodiment 1, except that the amount of heat-shrinkable fiber mesh added is 4.5 kg / m 3 , the rest are the same as in Example 1.
[0145] Example 3
[0146] The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete provided in the embodiment of the present application is the same as that in embodiment 1, except that the amount of heat-shrinkable fiber mesh added is 6 kg / m 3 , the rest are the same as in Example 1.
[0147] Comparative Example 1
[0148] The C80 concrete provided in this comparative example is the same as that in Example 1, except that no heat shrinkable fiber mesh is added, and the rest is the same as that in Example 1.
[0149] Comparative Example 2
[0150] The C80 concrete provided in this comparative example is the same as that in Example 1, except that the amount of heat shrinkable fiber mesh added is 6 kg / m 3 , using P·II 52.5 silicate cement instead of high-alumina phase cementitious material, and the rest is the same as Example 1.
[0151] Comparative Example 3
[0152] The C80 concrete provided in this comparative example is the same as that in Example 1, except that the amount of heat shrinkable fiber mesh added is 6 kg / m 3 , and no CaCO3 whiskers are added, and the rest are the same as in Example 1.
[0153] Performance Testing
[0154] The performance of the heat-shrinkable fiber mesh reinforced long-span box-arch C80 high-toughness concrete in Examples 1 to 3 and the concrete in Comparative Examples 1 to 3 were tested, and the results are shown in Table 1 below.
[0155] Table 1 - Properties of concrete in different embodiments and comparative examples
[0156]
[0157]
[0158] The above results show that the compressive strength of the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete obtained by the present invention is above 90MPa, and the flexural strength is above 10MPa, and it has excellent working performance, mechanical properties and volume stability. In addition, by comparing Example 1 with Comparative Example 1, it is found that the addition of the heat-shrinkable fiber mesh can effectively improve the strength and toughness of the concrete; by comparing Example 3 with Comparative Example 3, it is found that the addition of calcium carbonate whiskers reduces the working performance of the concrete, but improves the toughness index and mechanical properties of the concrete; by comparing Example 3 with Comparative Example 2, sulphoaluminate high-iron phase cement can effectively improve the bending toughness and volume stability of the concrete, and the addition of sulphoaluminate high-iron phase cement can greatly reduce the 56d volume shrinkage of the concrete.
[0159] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0160] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.
Claims
1. A heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete, characterized in that: Includes the following raw materials: high alumina phase cementitious material 580~640kg / m 3 , Fine aggregate 750~850kg / m 3 , high strength coarse aggregate 950~1100kg / m 3 , fiber reinforced materials 40~80kg / m 3 , heat shrinkable fiber mesh 3~8kg / m 3 , Special admixture for viscosity reduction and collapse prevention 9~11kg / m 3 , Water 140~160kg / m 3 .
2. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 1, characterized in that: The special admixture for reducing viscosity and preventing collapse comprises a mother solution of a polycarboxylic acid high-efficiency water-reducing agent, an air entraining agent, a retarder, boric acid, a tetramethyldecynediol foam control agent, an acrylic acid-modified organic silicon defoamer and water; The mass ratio of polycarboxylic acid high-efficiency water-reducing agent mother liquor, air entraining agent, retarder, boric acid, tetramethyldecynediol foam control agent, acrylic acid modified silicone defoaming agent and water is (52-56):(0.03-0.05):(1-2.5):(1.5-1.9):(0.05-0.2):(0.03-0.07):(33.65-35.15).
3. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 1, characterized in that: The heat-shrinkable fiber net is a mesh structure woven from heat-shrinkable fibers, wherein the heat-shrinkable fibers include a heat-shrinkable core material and a heat-shrinkable skin material coated on the outer periphery of the heat-shrinkable core material; The material of the heat shrinkable leather material includes at least one of polyvinyl alcohol, polyethylene, and polyoxymethylene; The molecular weight of the polyvinyl alcohol is 170,000 to 220,000; The molecular weight of the polyethylene is 1 million to 2 million; The molecular weight of the polyoxymethylene is 20,000 to 30,000; The heat shrinkable core material is made of polypropylene, and the molecular weight of polypropylene is 6000-8000; The heat-shrinkable fiber has a tensile strength of 500-1200 MPa, an elastic modulus of 7-35 GPa, a shrinkage rate of 0.5%-12%, and a response temperature of 30°C-100°C.
4. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 1, characterized in that: The high-alumina phase cementitious material comprises a mixture of P·II 52.5 silicate cement, P·II 42.5 sulphoaluminate high-iron phase cement, fly ash microspheres and silica fume; The P·II 42.5 sulphoaluminate high iron phase cement is a P·II 42.5 high iron phase sulphoaluminate cement containing a Q phase; The fly ash microbeads have a 28d activity index of 109% and a water requirement ratio of 101%; The SiO2 mass content in the silica ash is ≥90%, and the specific surface area is ≥20300m 2 / kg, 28d activity index ≥100%.
5. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 4, characterized in that: The P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method: Mix fly ash, limestone, magnesite and calcium sulfate to obtain a first mixed material; The first mixed material is heated to 1290-1350° C. at a rate of 5-10° C. / min, and calcined for 40-45 minutes to obtain Q phase-calcium sulfoaluminate clinker; Mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture; The second mixed material is heated to 1290-1350°C at a rate of 5-10°C / min and calcined, and kept at this temperature for 40-45 minutes to obtain Sulphoaluminate cement clinker; Q phase-calcium sulphoaluminate clinker, The sulphoaluminate cement clinker is mixed to obtain the Q-rich P·II42.5 high iron phase sulphoaluminate cement clinker; The Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker is mixed with dihydrate gypsum and ground to a specific surface area of 330-350m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained.
6. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 1, characterized in that: The fiber reinforcement material includes copper-plated straight steel fiber, multi-anchor steel fiber, heat-shrinkable fiber, and CaCO3 whisker; The mass ratio of the copper-plated straight steel fiber, the multi-anchor steel fiber, the heat-shrinkable fiber, and the CaCO3 whisker is (20-30):(20-30):(1-2):(10-15).
7. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 6, characterized in that: The copper-plated straight steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.20 ± 0.02 mm, a breaking strength of ≥ 2200 MPa, an elastic modulus of 190 to 230 GPa, and a tensile strength of 400 to 2100 MPa; The multi-anchor steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.18 ± 0.02 mm, a breaking strength of ≥ 1300 MPa, an elastic modulus of 220 to 240 GPa, and a tensile strength of 600 to 2200 MPa; The heat-shrinkable fiber has a length of 10 mm to 12 mm, a tensile strength of 500 to 1200 MPa, an elastic modulus of 7 to 35 GPa, a shrinkage rate of 0.5% to 12%, and a response temperature of 30°C to 100°C; The CaCO3 whisker has a nominal length of 10 to 20 μm, an elastic modulus of 410 to 710 GPa, and a tensile strength of 3000 to 6000 MPa.
8. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 5, characterized in that: The mass ratio of the fly ash, limestone, magnesite and calcium sulfate is (60-70):(15-20):(5-10):(5-10); The mass ratio of the red mud, limestone, bauxite and calcium sulfate is (40-45):(25-30):(20-25):(5-10); The Q phase-calcium sulphoaluminate clinker, The mass ratio of sulphoaluminate cement clinker is (50-60):(40-50); The mass of the dihydrate gypsum is 10-15% of the mass of the Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker; The amount of P·II 52.5 silicate cement added is 350-355 kg / m 3 , P·II 42.5 sulphoaluminate high iron phase cement addition amount is 150~155kg / m 3 , the amount of fly ash microbeads added is 80-90kg / m 3 , silica fume 30~40kg / m 3 .
9. The heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to claim 1, characterized in that: The fine aggregate is river sand with an apparent density of 2560-2650 kg / m 3 , fineness modulus is 2.8, water absorption ≤8%; The high-strength coarse aggregate is 5-16mm continuously graded basalt ultra-high-strength coarse aggregate with an apparent density of 2900-3000kg / m 3 .
10. A method for preparing the heat-shrinkable fiber mesh reinforced long-span box arch C80 high-toughness concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: The high-aluminum phase cementitious material, fine aggregate and high-strength coarse aggregate are mixed and stirred for 60 to 120 seconds, and then water and 45 to 55% by weight of a special admixture for reducing viscosity and preventing collapse are added, and the stirring is continued; the fiber reinforcement material is then added, and after stirring, the remaining special admixture for reducing viscosity and preventing collapse is added to obtain a mixture; The heat-shrinkable fiber mesh is fixed in the mold, and then the mixture is placed in the mold and vibrated to obtain the heat-shrinkable fiber mesh reinforced large-span box arch C80 high-toughness concrete.
Citation Information
Patent Citations
Concrete with low shrinkage, good erosion and abrasion resistance and ultrahigh toughness, and preparation method thereof
CN110451878A
High-flow-state low-shrinkage high-toughness fiber concrete and preparation method thereof
CN117024068A
High performance cement complex material composition containing high-content hybrid fiber reinforcement and concrete structure using the same
KR102525098B1